2016
DOI: 10.2147/ndt.s106039
|View full text |Cite
|
Sign up to set email alerts
|

The effects of psychiatric treatment on depression, anxiety, quality of life, and sexual dysfunction in patients with inflammatory bowel disease

Abstract: ObjectiveDepression and anxiety are common disorders in inflammatory bowel disease (IBD). Our aim is to prospectively determine the effect of psychiatric treatment on scores for depression, anxiety, quality of life (QoL), and sexual dysfunction in an outpatient population diagnosed with IBD and also anxiety and/or depression disorder.Patients and methodsPatients who scored higher than the cutoff point on the Hospital Anxiety Depression Scale were referred for further structured psychiatric evaluation and deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 34 publications
1
41
1
1
Order By: Relevance
“…3 Increased inflammatory bowel disease activity, abdominal and pelvic surgery, and depression have all been linked to sexual dysfunction. 35,36 Many studies have demonstrated that disease activity in IBD is strongly linked to depression and anxiety, [37][38][39] which in turn has been shown to increase symptoms of sexual dysfunction. 38,39 Active IBD in women is associated with reduced self-perception of attractiveness, sexual satisfaction, and sexual activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Increased inflammatory bowel disease activity, abdominal and pelvic surgery, and depression have all been linked to sexual dysfunction. 35,36 Many studies have demonstrated that disease activity in IBD is strongly linked to depression and anxiety, [37][38][39] which in turn has been shown to increase symptoms of sexual dysfunction. 38,39 Active IBD in women is associated with reduced self-perception of attractiveness, sexual satisfaction, and sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Many studies have demonstrated that disease activity in IBD is strongly linked to depression and anxiety, [37][38][39] which in turn has been shown to increase symptoms of sexual dysfunction. 38,39 Active IBD in women is associated with reduced self-perception of attractiveness, sexual satisfaction, and sexual activity. 40 However, data regarding disease activity as a reason for sexual dysfunction are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive behavioural therapy has been found to improve symptoms of depression and quality of life among IBD patients . Pharmacological therapy in the form of selective serotonin reuptake inhibitors and tricyclic antidepressants has improved psychiatric symptoms, quality of life and IBD disease activity . Given the existence of effective treatments with the potential for significant clinical and psychological impact, interventions targeting screening and treatment for anxiety and depression at both the preoperative and postoperative surgical visits may be of significant clinical utility.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pharmacological therapy for mood disorders may have the potential to alter the natural history of CD and UC. Limited data, to date, have suggested improvements in mood, inflammatory activity, and quality of life with antidepressant therapy [ 23 , 38 ]. Our own longitudinal follow-up data did not show any statistically significant differences in the proportion of patients experiencing endpoints consistent with inflammatory activity, according to use of antidepressants at baseline.…”
Section: Discussionmentioning
confidence: 99%